Pyruvate kinase is necessary for Brucella abortus full virulence in BALB/c mouse. (December 2016) - Gao, Jianpeng; Tian, Mingxing; Bao, Yanqing; Li, Peng; Liu, Jiameng; Ding, Chan; Wang, Shaohui; Li, Tao; Yu, Shengqing
Abstract Brucellosis, caused by a facultative intracellular pathogenBrucella, is one of the most prevalent zoonosis worldwide. Host infection relies on several uncanonical virulence factors. A recent research hotpot is the links between carbon metabolism and bacterial virulence. In this study, we found that a carbon metabolism-related pyruvate kinase (Pyk) encoded bypyk gene (locus tag BAB_RS24320) was associated withBrucella virulence. Determination of bacterial growth curves and resistance to environmental stress factors showed that Pyk plays an important role inB. abortus growth, especially under the conditions of nutrition deprivation, and resistance to oxidative stress. Additionally, cell infection assay showed that Pyk is necessary forB. abortus survival and evading fusion with lysosomes within RAW264.7 cells. Moreover, animal experiments exhibited that the Pyk deletion significantly reducedB. abortus virulence in a mouse infection model. Our results elucidated the role of the Pyk inB. abortu s virulence and provided information for further investigation ofBrucella virulence associated carbon metabolism.